PCL/PVA nanoencapsulated reinforcing fillers of steam exploded/autoclaved cellulose nanofibrils for tissue engineering applications. Issue 31 (8th April 2015) - Manhas, Navdeep; Balasubramanian, K.; Prajith, P.; Rule, Prashant; Nimje, Sunil
<x xml:space="preserve">Abstract</x> The process of extraction of cellulose nanofibrils by steam explosion followed by electrospinning with biodegradable polymers to yield PCL/PVA nanoencapsulated cellulosic reinforcing fillers for tissue engineering applications.